EVALUASI PENGELOLAAN DANA DESA DI KAMPUNG YOBEH DISTRIK SENTANI KABUPATEN JAYAPURA - Marcelino Latukolan; Yosephina Ohoiwutun (JURNAL KEBIJAKAN PUBLIK, 2022)
This article focuses on the study of Evaluation of Village Fund Management in Yobeh Village, Sentani District, Jayapura Regency, with the aim of analyzing and evaluating village fund management in Yobeh Village and knowing the factors that influence the Village Fund management process in Yobeh Village, Sentani District, Jayapura Regency. To determine the success of village fund management in Yobeh village, the author uses William Dun's theory of policy evaluation which divides policy evaluation into Effectiveness, Efficiency, Sufficiency, Equality, Responsiveness, and Accuracy, then to analyze more deeply about the management of village funds, the author refers to Minister of Home Affairs Regulation No. 20 of 2018 concerning Village Financial Management which regulates the Principles of Village Financial Management. Furthermore, to analyze the factors that affect the management of village funds, the authors refer to Permendagri No. 20 of 2018 concerning Village Financial Management, it regulates the stages of village financial management and then combines them with the results of interviews and observations in the field so that conclusions and solutions can be obtained to improve village fund management in Yobeh Village, Sentani District, Jayapura Regency.